Implementation of National Assessment - Desi Rahmawati; Supadi; Rugaiyah; Muhammad Fadholi (Universitas Pendidikan Ganesha, 2024)
The quality of education, based on the results of the PISA study, shows a lag compared to other countries. Efforts to improve this quality through the National Assessment (AN) program still need to overcome various obstacles, especially in implementation and follow-up. This study aims to evaluate strategies to optimize AN implementation, identify solutions to the challenges faced, explore school programs that support students facing AN, and analyze school follow-up on AN results. This study used a qualitative approach with an evaluative descriptive design. The research subjects comprised teachers, principals, and vice principals, as well as 15 students from various levels taken as samples to represent the school population. Data were collected through observation, interviews, and documentation using instruments like interview guidelines and observation sheets. Data analysis was conducted using data reduction, data presentation, and conclusion-drawing techniques, with triangulation of methods and sources as data validation. The results showed that AN optimization strategies include strategic planning, improving teacher competence, and utilizing digital technology. Solutions for implementation constraints include improving infrastructure and intensive training for teachers. School programs that support students include intensive guidance and assessment simulations. In conclusion, AN can be optimized by strengthening planning, training, and technical support. The implication of this research is the need for sustainable policies to improve the readiness of schools and teachers to face AN.